Incarceration exposure during pregnancy and maternal disability: findings from the Pregnancy Risk Assessment Monitoring System - Alexander Testa; Chantal Fahmy; Dylan B. Jackson; Kyle T. Ganson; Jason M. Nagata (BMC, 2022)
Abstract Background Extant research reveals that currently and formerly incarcerated individuals exhibit higher rates of disability. Moreover, recent research highlights that women exposed to incarceration during pregnancy -either personally or vicariously through a partner- face poorer health. However, prior research has not detailed the connection between incarceration exposure and risk for maternal disability. Methods The aim of this study is to evaluate the association between a women's exposure to incarceration during pregnancy and disability including difficulty with: communication, hearing, remembering, seeing, self-care, or walking. Data are from Pregnancy Risk Assessment Monitoring System (PRAMS), 2019 (N = 12,712). Logistic and negative binomial regression were used to assess the relationship between incarceration exposure and maternal disability. Results Among the sample of women who delivered a recent live birth, approximately 3.3% of the sample indicated they were personally or vicariously exposed to incarceration in the 12 months before birth. Compared to those who did not have incarceration exposure, women with incarceration exposure have elevated odds of several disabilities, including difficulty remembering (Adjusted Odds Ratio [AOR] = 1.971; 95% Confidence Interval [CI] = 1.429, 2.718), difficulty seeing (AOR = 1.642, 95% CI = 1.179, 2.288), difficulty walking (AOR = 1.896, 95% CI = 1.413, 2.544), and a greater number of cumulative disabilities (Incidence Risk Ratio [IRR] = 1.483; 95% CI = 1.271, 1.731). Conclusions Women personally or vicariously exposed to incarceration during pregnancy endure greater odds of having a disability. Considering both incarceration and disability are important public health issues with implications for maternal and child well-being, these findings highlight the need for further research that can better understand the connection between incarceration and disability.